BEP/SEP and Outage Performance Analysis of 𝐿-Branch Maximal-Ratio Combiner for 𝜅-𝜇 Fading - Mirza Milišić; Mirza Hamza; Mesud Hadžialić (International Journal of Digital Multimedia Broadcasting)
Maximal-ratio combiner (MRC) performances in fading channels have been of interest for a long time, which can be seen by a number of papers concerning this topic. In this paper we treat bit error probability (BEP), symbol error probability (SEP) and outage probability of MRC in presence of 𝜅-𝜇 fading. We will present 𝜅-𝜇 fading model, probability density function (PDF), and cumulative distribution function (CDF). We will also present PDF, CDF, and outage probability of the L-branch MRC output. BEP/SEP will be evaluated for broad class of modulation types and for coherent and noncoherent types of detection. BEP/SEP and outage performances of the MRC will be evaluated for different number of branches via Monte Carlo simulations and theoretical expressions.